Use of smartphone of form lay or your use specialized in school environment - Julio César,; Awdry Feisser,; Sani de Carvalho Rutz, (Uni-pluriversidad, 2017)
This research to collected texts of educational institutions, state and federal laws, and of the manifest of the those involved with the regulation regarding the cellphone within the classroom, to collected on institutional websites and in newspaper as website. It was also to take science of the NMC Horizon Report document (2015), with suggestions of short technological innovations, medium and long term, and to inserts technology in education, which served as reference for analysis of the collected texts. However, it found gaps in epistemological or philosophical terms about the technology concept of the NMC document. We used the French strand of discourse analysis, highlighting the ideological bias of those who are technology users, among which by hypothesis cannot understand the mediation that these technologies could promote the teaching and learning processes. Of the analysis, it was to infer that there is divergence between the texts of the NMC Horizon Report. It was to compare with the texts of those public officials who to legislated laws or who to judge the application of laws or to wove rules, for to use of technology in scholar scope. It was to conclude for the to need of the to approach of those who to think education with inserts of new technological tools, those who to build the rules governing the teaching, so that together in a collaborative process, promote yourself constructive aspects of mediation of the use of technology in contributing in training of students, as negotiators from the world of science and technology, with a to use conscious and specialized of the cellphone.